Clinico-pathological initial outcome of a newly adopted novel surgical technique for nodal metastatic thyroid cancer at a large-volume centre in a high-income developing country - Hassan, Iyad; Hassan, Lina; Bacha, Farooq; Alsalameh, Mohammad; Qatee, Omran; Hassan, Wiam (Frontiers in Surgery, 2023)
In the past decade, the incidence of lymph node metastasis of thyroid cancer has increased, and so has the patient demand for a smaller scar. This research reports the surgical and patho-oncological short-term outcomes of a novel, minimally invasive neck dissection approach for nodal thyroid carcinoma at single endocrine surgery centre. This study employed a prospectively maintained surgical database to retrospectively analyse surgical complications, including bleeding, hypocalcaemia nerve injury and lymphatic fistula, as well as oncological metrics such as the type of tumour and the ratio of lymph node metastasis to the number of harvested lymph nodes in 100 patients that underwent open minimally invasive selective neck dissection. The study comprised 50 patients with thyroidectomy, with bilateral central compartment neck dissection (BCCND; 50%); 34 with thyroidectomy, BCCND and selective bilateral lateral compartment neck dissection (BLCND; 34%); and 16 patients with selective unilateral central and lateral compartment neck dissection by recurrent nodal disease (ULCND; 16%). The female-to-male gender ratio was 78:22, with median ages of 36 and 42 years, respectively. Histopathology findings revealed that 92% of patients had papillary thyroid cancer (PTC) and 8% had medullary thyroid cancer. The mean total number of lymph nodes removed was 22 in the BLCND group, 17 in the ULCND group and 8 in the BCCND group (p = 0.001). Furthermore, the average lymph node metastasis was significantly higher in the BLCND group (p = 0.002). The percentage of temporary hypoparathyroidism was 29.8% and it persisted for 1.3%. The lateral compartment dissection morbidity was as follows: Four male patients with tall cell infiltrative PTC presented with pre-existing vocal cord paresis, necessitating nerve resection and anastomosis, and two more developed it after surgery (1.1% of the nerve at risk). Lymphatic fistulas occurred in four patients (4%) who were treated conservatively. Two patients were readmitted due to symptomatic neck collection. Horner syndrome was discovered in just one female patient. Male gender, aggressive histology and lateral compartment dissection independently increased surgical morbidity. In a high-volume endocrine centre, the adoption of minimally invasive selective neck dissections to treat nodal metastatic thyroid cancer did not increase specific cervical surgery complications.